The Legal System Regarding Subsidies Allocation for Local Government in Thailand - Pakasapasut, Khattiya (Journal of Multidisciplinary Academic Research and Development (JMARD), 2025)
The objective of this thesis is to study the legal criteria that are the basis of authority in determining the allocation of subsidies to local administrative organizations. Including legal criteria that set the framework for spending subsidies of local government. From the study, there are legal problems are founded: The first problem is conflict with the principles of fiscal independence of local government. And the second problem is the problems with legal criteria regarding the allocation and spending of subsidies to local government organizations to carry out missions that have been improperly transferred from the central government which are unequal and unfair. Each of those issues has sub-problems that must be considered. Suggestions of those problems above: the author proposes to amend laws: the Act on Decentralization Plans and Procedures for Local Administrative Organizations 1999 which was amended in 2006. The regulations of the Thai Ministry of Home Affairs regarding budgetary methods of local government 2020. In order to establish the legal framework for allocation. To spend subsidies of local government in accordance with the principles of independence of local government. Including to be fair and equal for local government. The framework for subsidy allocation must be more clearly defined. And to take into account the potential and size of local government that differ in their fiscal status. In addition, setting the framework of criteria that gives authority to the Ministry of Interior. The Ministry of Interior must not encroach too much on the fiscal independence of local government.